(untitled) (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
This study aims to analyze the effect of profit sharing ratios on mudharabah deposits in Islamic banks in Indonesia during the 2018-2022 period. The research method used is secondary research. Hypothesis testing in this study was carried out using simple linear regression analysis using panel data from the annual financial reports of 10 Islamic banks in Indonesia registered with the Financial Services Authority (OJK) in 2022. This analysis uses SPSS version 22 software. The results of the study reveal that the impact of the profit sharing ratio on total mudharabah deposits is explored through a simple linear regression equation: Y = 11.705 + 0.187X + e The coefficient of the impact of the profit sharing ratio on mudharabah deposits is statistically significant, with a calculated t value of 2.238 which exceeds the t table value of 0.67906. This indicates rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). The coefficient of determination of 0.095 indicates that about 9.5% of the variation in mudharabah deposits can be explained by variations in the profit sharing ratio. The remaining 90.5% is influenced by other factors not included in this model.